APLIKASI PENGHITUNG UPAH LEMBUR BERDASARKAN JUMLAH WAKTU LEMBUR DENGAN MENGGUNAKAN ALGORITMA LINEAR SEARCH - Hendra Kurniawan; Sabar Rudiarto (PETIR, 2019)
The development of information technology has created many solutions to problems that are often faced in life. An application can help a job and make it easier has encourage companies to use applications that help their work in several departments such as administration and human resources. Some companies have regulations requiring employees to do work more than normal working hours that called overtime. Every employee who does overtime will get overtime wages accordance to the amount of overtime that has been done. But sometimes the late of payments occurred because the calculation of overtime wages takes a long time when many employees did overtime. To solve this problem the company needs an application that can calculate overtime wages quickly and accurately, using the linear search algorithm application will search and process the recorded data in the attendance machine, then calculate overtime wages according to the amount of overtime that has been done. And then it can minimize the occurrence of late payments and more accurate calculations result.